Analisis Evaluasi Formatif di SD Negeri 05 Cipondoh - Mahardhika, Gita; Lubis, Nur Sania (Lembaga Yasin AlSys, 2022)
Evaluation is carried out to measure the success or failure of the activity or learning process. This can be seen through the learning outcomes achieved by students which show the success of educators in managing these activities. In addition, with evaluation, educators can measure the extent to which students can capture or absorb the knowledge conveyed by the educator. The type of evaluation in this study is formative evaluation. Formative evaluation is an evaluation that is carried out while the program is still in progress or when the program is still approaching the start of activities. The purpose of formative evaluation is to find out the extent to which the designed program can run, as well as identify obstacles.